Peningkatan Pemahaman Konsep Globalisasi dengan Model Belajar Behavioristik di Kelas VI SDN Bendogerit 2 Kota Blitar - Sri Kusanti (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
Social Sciences (IPS) can help students gain a fundamental understanding of history, economics, geography, and other social sciences. Through social studies subjects, students are directed to be able to become democratic and responsible Indonesian citizens and peace-loving citizens of the world. Social studies subjects are arranged systematically, comprehensively, and integrated in the learning process. Social studies learning at the UPT Education Unit of SDN Bendogerit 2 Blitar City on Globalization, is still not well implemented and gets a score that is still less than the KKM. In this case the teacher must instill about the position of students in the era of globalization in order to filter the entry of foreign influences into Indonesia. Learning outcomes obtained from pre-action learning can be seen from 29 students who achieved completeness only as many as 10 students or 34%. In accordance with this, the teacher conducts classroom action research, with qualitative descriptive research, using a learning model that can increase students' understanding of concepts, namely the Behavioristic learning model. Behavioristic learning model is a learning model that emphasizes the conditioning of the learning environment so that student behavior can be formed or changed as expected.